(untitled) (Revista Contexto & Educação, 2025)
Violence prevention work must use various methodological and participatory strategies, such as the use of educational materials produced based on local reality. Thus, the objective is to describe the process of production, evaluation, and validation of a game that addresses the topic of Bullying in schools. Participatory research, completed in the first half of 2023, developed in four stages: 1- Holding a workshop to create Educational Materials with teachers; 2- Creation of a storyboard by researchers; 3- Evaluation of the game produced by the target audience; and 4- Validation of the game by judges. Research approved by the ethics committee. Fifteen teachers participated and produced the game “Beat Bullying”. Initially, the researchers created a provisional storyboard that, after evaluation by teachers and changes, materialized into a card game with the theme of bullying, which was evaluated by nine elementary school II students. For content validation, 14 health judges participated and issued an overall ICV of 0.91 for the game, which was approved as an educational tool that stimulates knowledge acquisition and behavior change. The material produced, consisting of a flapbook, 55 cards (40 answer cards, 8 number cards and 7 action cards), a dice, a roulette wheel and a manual, aims to contribute to the discussion of school violence with adolescents and assist the work of education and health professionals in reducing vulnerabilities involving the topic of violence.